2020
DOI: 10.3390/ani10112118
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of BPI Expression on Escherichia coli F18 Infection in Porcine Kidney Cells

Abstract: The efficacy and regulatory activity of bactericidal/permeability-increasing protein (BPI) as a mediator of Escherichia coli (E. coli) F18 resistance remains to be defined. In the present study, we evaluated lipopolysaccharide (LPS)-induced changes in BPI gene expression in porcine kidney (PK15) cells in response to E. coli F18 exposure. We additionally generated PK15 cells that overexpressed BPI to assess the impact of this gene on Toll-like receptor 4 (TLR4) signaling and glycosphingolipid biosynthesis-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Some commensal E. coli strain can produce colicin, an AMP effective against pathogenic E. coli; Cutler and colleagues proved that its addition in diets of weanling piglet challenged with E. coli decreases PWD incidence and reduces the expression of pro-inflammatory cytokines [211]. Finally, it has been demonstrated that the in vitro overexpression of the BPI antimicrobial peptide can help in reducing ETEC adhesion to target cells and modulating the expression of several inflammatory cytokines [212].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…Some commensal E. coli strain can produce colicin, an AMP effective against pathogenic E. coli; Cutler and colleagues proved that its addition in diets of weanling piglet challenged with E. coli decreases PWD incidence and reduces the expression of pro-inflammatory cytokines [211]. Finally, it has been demonstrated that the in vitro overexpression of the BPI antimicrobial peptide can help in reducing ETEC adhesion to target cells and modulating the expression of several inflammatory cytokines [212].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%